Portrait of an unknown woman [large type] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series, 2022)
"A gripping story of deception in the world of international fine art. Restorer and spy Gabriel Allon embarks on a dangerous hunt across Europe for the secret behind the forgery of a seventeenth-century masterpiece that has fooled experts and exchanged hands for millions"--